Mitos y juegos de lenguaje - Gutiérrez Estévez, MANUEL (Revista Española de Antropología Americana, 2003)
In this paper the author defends that there are not «myths», but language games and this games use a traditional repertory like raw material. The repertory is traditional, but always remodeled, with multifaceted happenings and characters.